2018
DOI: 10.4103/jcd.jcd_123_18
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of remineralizing efficacy of biomimetic self-assembling peptide on artificially induced enamel lesions: An in vitro study

Abstract: Background:The biomimetic self-assembling peptide technology is a paradigm for dental hard tissue regeneration.Aim:To investigate the efficacy of biomimetic self-assembling peptide (P11-4) on enamel remineralization compared to casein phosphopeptide-amorphous calcium phosphate fluoride (CPP-ACPF) and fluoride-based delivery systems.Materials and Methods:Artificial enamel lesions were created on buccal surfaces of 40 extracted human molars. Specimens were randomly assigned to four groups (n = 10) according to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Critical clinical assessment factors such as the hardness and gloss of the lesion could not be taken into account as they could not be measured reliably within an in vivo study. It would be interesting to measure the enamel hardness induced by SAP P 11 -4, and compare those to the previously reported in vitro microhardness results 34,35 .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Critical clinical assessment factors such as the hardness and gloss of the lesion could not be taken into account as they could not be measured reliably within an in vivo study. It would be interesting to measure the enamel hardness induced by SAP P 11 -4, and compare those to the previously reported in vitro microhardness results 34,35 .…”
Section: Discussionmentioning
confidence: 87%
“…exhibited a substantial decrease of impedance readings throughout the study period (Table 1). Control teeth showed a mean baseline value of 42.0 at day 0, which decreased to 35.0 at day 45,29.5 at day 90, and 33.7 at day 180. Test teeth showed a mean baseline value of 46.7 and exhibited a markedly larger decrease to 21.1 (day 45), 18.4 (day 90), and 19.7 (day 180).…”
Section: Impedance Measurement Of White Spot Lesion (Primary Endpointmentioning
confidence: 95%
“…Recently, a rationally designed monomeric self-assembling peptide P 11 -4 (SAP P 11 -4) solution 9 , which is able to diffuse into the subsurface carious lesions and self-assembles into a 3D biomimetic scaffold within, can guide the remineralization process 10,11 . SAP P 11 -4 has been shown to diffuse into the body of the carious lesion, and supporting de novo hydroxyapatite formation below the porous mineralized surface [11][12][13][14] . A first in man clinical trial has shown that SAP P 11 -4 is safe for human use and can reverse caries progression, significantly reducing the size of buccal white spot lesions as assessed by a visual analogue scale 15 .…”
mentioning
confidence: 86%
“…A variant of CPP-ACP known as biomimetic self-assembling peptide (P11-4) has shown significantly high remineralising efficacy compared to topical fluorides and CPP-ACPF exhibiting its potential as a non-invasive enamel regenerative material. 26 These compounds have been recommended to be commercially added to foods, soft drinks and chewing gum, as well as in toothpastes and mouthwashes to control dental caries.…”
Section: Adverse Aspectsmentioning
confidence: 99%